Prevalence of Fasciolosis in Commercial Cattle Farm of Tilottama Municipality, Rupandehi, Nepal - Bhusal, N.; Bhatta, B. R.; Shrestha, S.; Chapagain, A. (Journal of the Institute of Agriculture and Animal Science, 2020)
Fasciolosis is a common parasitic disease affecting cattle and other ruminants, caused by Fasciola hepatica and Fasciola gigantica. The disease is widely distributed and can cause extensive economic losses to the farmers and the national economy. A cross sectional study was conducted to determine the prevalence of fasciolosis in commercial cattle farms of Tilottama Municipality, Rupandehi district, Nepal. A total of 270 fresh faecal samples were collected purposively from the study area with different ages, sex, stages, and breeds for faecal examination (sedimentation method) to diagnose eggs of Fasciola in the collected samples. The obtained data were coded and analysed using Microsoft Excel 2016. The overall prevalence of fasciolosis in cattle was found 15.56%. Age and sex wise prevalence was found statistically significant (P<0.05) while stage and breed wise prevalence was insignificant (P>0.05). Therefore, fasciolosis is prevalent moderately among cattle in Tillottoma municipality, which necessitates the study of detailed epidemiology of the disease and effective control strategies against it in order to prevent huge economic losses.